Supervisory Communication and Employees’ Job Satisfaction in the Small and Medium-Sized Enterprises (SMEs) - Ibrahim, Mohd Nazri; Abdullah, Zaridah; Md Syed, Md Azalanshah; Yatim, Muhammad Amanullah (Universiti Kebangsaan Malaysia Press, 2018)
Supervisory communication has been determined as a strong factor in predicting organizational environment. Even though it is not clearly outlined, supervisory function serves as a big determining factor in job satisfaction. Despite the fundamental idea that small and medium-sized enterprises (SMEs) contribute to the development of the nation, there is still a huge gap on how organizational communication works particularly in relation to how well the small numbers of employees in SMEs could interact with their supervisors. This study examines the relationship between supervisory communication and job satisfaction among SMEs’ employees in Klang Valley, Malaysia. It was hypothesized that supervision is a determining factor to job satisfaction due to the fact that the relationship between supervisors and subordinates in the workplace is essential. Secondly, supervisory communication is imperative as it is important to influence subordinates’ job satisfaction. 184 respondents were selected randomly from SMEs’ directory for this research. The study found that there is a moderately strong relationship between supervisory communication and job satisfaction among employees in the industry. Specifically, supervisory communication explained 39.5% of the communication satisfaction variance. Therefore, supervisory communication significantly predicted job satisfaction in the industry. This study underlines the importance of supervisory communication towards job satisfaction and predicted that it will finally contribute to the future development of the industry.